Investigation of material removal characteristics in EDM of nonconductive ZrO2 ceramic - Sabur, Abdus; Ali, Mohammad Yeakub; Maleque, Md. Abdul; Khan, Ahsan Ali (Elsevier, 2013)
The use of nonconductive ceramic materials is increasing rapidly in industrial and engineering applications due to its high hardness, low thermal conductivity, and resistance to oxidation. Machining operations for fabricating structures from nonconductive ceramic materials are difficult and most of the traditional machining techniques are not applicable because of its high brittleness. Electro discharge machining (EDM) technique, a noncontact machining process, is applied for processing nonconductive ceramic ZrO2 using assisting electrode. In this technique, pyrolytic carbon layer on the ceramic surface formed by the cracked carbon from the carbonic dielectric, plays the key role for continuous EDM. The formation of pyrolytic carbon and its stability depends upon the input power, workpiece material, tool electrode material, dielectric substance, polarity, and discharge duration. In this study, experiments were done to investigate the effect of input power on the material removal rate (MRR) and to explore the material removal mechanism. The experimental results show that the material is removed in EDM of nonconductive ZrO2 ceramic mostly by spalling and it increases with the increase of input power.